(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
Monetary policy is the set of actions through which a central bank manages money and credit conditions to achieve macroeconomic objectives—most prominently price stability, alongside maximum sustainable employment, financial stability, and, in many economies, exchange‑rate stability. In practice, this means steering short‑term interest rates, influencing liquidity and expectations, and ensuring the monetary and financial system transmits policy to households and firms (CFI; ECB).